Effect of Vehicle-Parapet Collision Forces on Bridge Girders, Bracings, and Support Bearings - Elnassar, Zeinah Mohamad (2022)
A Master of Science thesis in Civil Engineering by Zeinah Mohamad Elnassar entitled, “Effect of Vehicle-Parapet Collision Forces on Bridge Girders, Bracings, and Support Bearings”, submitted in June 2022. Thesis advisor is Dr. Sami Tabsh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).